Uma proposta de formação do empreendedor visagista apoiada por aplicativos de inteligências artificiais: novos desafios, novas competências - Trindade, Robson Amauri (2023)
The overall objective of this research is to study how to train professionals in the beauty industry, considering current concepts that involve visagism, entrepreneurial education, and artificial intelligence. The justification for this research is that, although various scholars understand that visagism and artificial intelligence can be valuable tools for simulating and constructing new personal and professional images, there is a scarcity of academic research on how to train entrepreneurs in the beauty industry who already work with the integration and adaptation of digital images for application in personal and business projects. Given the (general and specific) objectives, we consider the following problematizing question: how to train entrepreneurs in the beauty industry, considering the opportunities generated through the integration of concepts and practices involving visagism, entrepreneurial education, and artificial intelligence? We opted for a qualitative scientific research methodology, following the exploratory approach, based on bibliographic/documentary data, since this research addresses theoretical and empirical aspects, with the aim of fulfilling its general objective. The review of previous studies related to the proposed topic focused primarily on the period between 2018 and 2023, encompassing books, scientific articles, theses, and dissertations, considering research available in the following online databases: a) PUC-SP Thesis and Dissertations Database (Pontifical Catholic University of São Paulo), b) Cape Thesis and Dissertations Database, c) The International Journal of Computer Game Research, d) Google Scholar. Articles available in the Scientific Electronic Library Online - SciELO were also considered for the review of previous studies, from scientific journals classified as level A1 to A4 in the Qualis-Capes, in the interdisciplinary and computer science area. The theoretical frameworks that support this investigation are the concepts of visagism, entrepreneurial education, and artificial intelligence. The data collection instruments for the interviewees were questionnaires, interviews, and observation. The context of the interviews involved professionals, teachers, and students in the beauty industry. Considering the information collected in the interviews, our reflections are organized into 5 categories: a) training of professional-visagist-teachers who teach the entrepreneurship discipline; b) teaching entrepreneurship in curricula of courses in the field of visagism: perspectives with its creation; c) teaching plan and activities developed; d) presence of the entrepreneurship discipline in the curriculum; e) entrepreneurship education methodology. These reflections contributed to the development of the proposal for training entrepreneurs in the beauty industry, supported by foundations of visagism, entrepreneurial education, and artificial intelligence